THE POTENTIAL OF CPEC IN PROMOTING CULTURAL HERITAGE AND TOURISM DEVELOPMENT IN PAKISTAN - Seema Gul; Imran Ur Rahman; Aisha Iftikhar; Dr. Noor Mohammad; Misbah Haque; Muhammad Fahim Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This review paper examines the potential of the China-Pakistan Economic Corridor (CPEC) in promoting tourism development and cultural heritage in Pakistan. It highlights the diverse tourism opportunities in Pakistan and the challenges that need to be addressed. The paper also proposes three approaches for promoting tourism in Pakistan: digital technologies for tourism promotion, public-private partnerships for infrastructure development, and sustainable tourism development. The paper concludes by emphasizing the need for a concerted effort from the government, private sector, and civil society to fully realize the potential of CPEC in promoting tourism development and cultural heritage in Pakistan.